Quality of wheat silage produced under different levels of nitrogen dressings at two phenological stages - Wrobel, Felipe de Lima; Neumann, Mikael; Leão, Guilherme Fernando Mattos; Sandini, Itacir Eloi; Poczynek, Mailson; Marafon, Fabiano (Revista de Ciências Agroveterinárias, 2018)
The objective was to evaluate the effects of two content levels of nitrogen dressing (88 kg ha-1 and 148 kg ha-1) in the wheat silage production of BRS Umbu harvested during two phenological stages (pre-flowering and floury grain). The production of fresh dry phytomass as well as morphological and chemical composition of silages were evaluated. This study used a randomized blocks design with a 2x2 factorial structure, with two content levels of nitrogen dressing and at two different harvest stages, with four replications. There was interaction (p<0.05) between levels of nitrogen dressing and phenological harvest stages for neutral detergent fiber (NDF) and acid detergent fiber (ADF) of silage. The wheat with a level of 88 kg N ha-1 and harvested at the phenological stage of floury grain had the lowest NDF (57.52%) and ADF (34.62%), compared to the cultivation with content of 148 kg N ha-1. Harvest during pre-flowering promoted higher production of fresh phytomass (25.178 to 20.646 kg ha-1); however, there was higher production of dry matter in the floury grain stage (9.792 to 4.808 kg ha-1). Crude protein was higher in silage harvested during pre-flowering compared to the floury grain stage, with 11.55% and 6.96%, respectively. Based on joint analysis of the results, wheat silage harvested at the stage of floury grain and with nitrogen dressing of 88 kg ha-1 had the best production and nutritional outcomes.